Ecology and signal structure drive the evolution of synchronous displays. (20th September 2019) - Perez, Daniela M.; Crisigiovanni, Enzo L.; Pie, Marcio R.; Rorato, Ana C.; Lopes, Sergio R.; Araujo, Sabrina B.L.
Abstract: Animal synchrony is found in phylogenetically distant animal groups, indicating behavioral adaptations to different selective pressures and in different signaling modalities. A notable example of synchronous display is found in fiddler crabs in that males wave their single enlarged claw during courtship. They present species‐specific signals, which are composed of distinctive movement signatures. Given that synchronous waving has been reported for several fiddler crab species, the display pattern could influence the ability of a given species to sufficiently adjust wave timing to allow for synchrony. In this study, we quantified the wave displays of fiddler crabs to predict their synchronous behavior. We combined this information with the group's phylogenetic relationships to trace the evolution of display synchrony in an animal taxon. We found no phylogenetic signal in interspecific variation in predicted wave synchrony, which mirrors the general nonphylogenetic pattern of synchrony across animal taxa. Interestingly, our analyses show that the phenomenon of synchronization stems from the peculiarities of display pattern, mating systems, and the complexity of microhabitats. This is the first study to combine mathematical simulations and phylogenetic comparative methods to reveal how ecological factors and the mechanics of animal signals affect the evolution of the synchronous phenomena.